Peran Pendidikan IPS dalam Menguatkan Identitas Budaya Masyarakat Tolitoli: Perspektif Guru dan Siswa: Penelitian - Hamna; Marshanda Intan Handayani; Nur Fadila Rusli; Winda Araroh (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Strengthening local cultural identity is important in the current era of modernization and globalization. There are various foreign cultures and trends that can erode local culture in society so that the field of education is required to actively contribute. This article aims to examine the role of social studies education in strengthening the cultural identity of the Toli-Toli community by reviewing it from the perspective of teachers and students. This research method adopts a qualitative approach with data collection techniques in the form of observation and interviews with teachers and students at SDN 26 Toli-Toli. The findings show that social studies learning carried out in schools plays a major role in introducing students to local culture, namely that which develops in Toli-Toli. Students are known to be able to learn and get to know many cultures such as regional languages, traditional houses, music, dances, traditional ceremonies, and various other cultures that are the identity of Toli-Toli Culture. Teachers carry out learning through images, videos, and culture-based projects so that students are interested and active in activities. This is able to build awareness for students in preserving local culture so that it makes a major contribution to strengthening the cultural identity of the Toli-Toli community. Thus, schools through the development of synchronization in continuing to integrate the content of the local cultural context into social studies learning in schools.